2016
DOI: 10.18632/oncotarget.13014
|View full text |Cite
|
Sign up to set email alerts
|

Sphingosine kinase 1 is a potential therapeutic target for nasopharyngeal carcinoma

Abstract: Sphingosine kinase 1 (SPHK1) has been shown to be involved in the progression of various types of human cancers. We previously demonstrated that SPHK1 is overexpressed and associated with clinical stage, locoregional recurrence, distant metastasis and poor prognosis in nasopharyngeal carcinoma (NPC). However, the biological roles involving SPHK1 and its potential usefulness as a therapeutic target in NPC remain unknown. In this study, Blocking SPHK1 using siRNA or FTY720 (a SPHK1 inhibitor) significantly reduc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
6
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 42 publications
1
6
0
Order By: Relevance
“…A previous study indicated that inhibition of SPHK1 activity by treatment with safingol markedly potentiated epigallocatechin gallate-induced apoptotic activity in vitro and in vivo (32). The results of the present study were consistent with several studies on other cancer types (33)(34)(35). In addition, inhibition of SPHK1 was demonstrated to sensitize TC cells to chemotherapeutic drugs, including 5-fluorouracil, docetaxel, doxorubicin and cisplatin.…”
Section: Discussionsupporting
confidence: 91%
“…A previous study indicated that inhibition of SPHK1 activity by treatment with safingol markedly potentiated epigallocatechin gallate-induced apoptotic activity in vitro and in vivo (32). The results of the present study were consistent with several studies on other cancer types (33)(34)(35). In addition, inhibition of SPHK1 was demonstrated to sensitize TC cells to chemotherapeutic drugs, including 5-fluorouracil, docetaxel, doxorubicin and cisplatin.…”
Section: Discussionsupporting
confidence: 91%
“…Assays were performed as described in our previous report [28,29]. Briefly, cell viability was measured using a Cell Counting Kit-8 (Dojinodo, Shanghai, China) according to the manufacturer's instructions.…”
Section: Cell Viability and Colony Formation Assaysmentioning
confidence: 99%
“…The wound-healing and migration assays were performed using previously described methods [ 44 ]. Cell migration was measured using a Transwell chamber (24-well insert, 8-Ī¼m pore size, Millipore, Massachusetts, USA).…”
Section: Methodsmentioning
confidence: 99%